Kemampuan Siswa Field Dependent Level Multistructural dalam Menyelesaikan Soal Pythagoras dan Pemberian Scaffolding - Siti Na’imah; I Made Sulandra; Rustanto Rahardi (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aimed to describe the ability of multilateral FD students to solve the problem of Pythagoras and its scaffolding. The data collection begins with GEFT and test 1. The subject's examination process is analyzed based on the SOLO taxonomy to see its level of ability. The results showed that the ability of multistructural level FD subjects could use some of the information provided for problem solving, but the answer given was not accurate. Scaffolding efforts to increase the level of FD students' ability from multistructural level to relational level consist of reviewing, restructuring, and developing contextual thinking. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kemampuan siswa FD level multistructural dalam menyelesaikan soal Pythagoras dan pemberian scaffolding. Pengumpulan data diawali dengan pemberian GEFT dan soal tes 1. Proses penyelesaian yang dilakukan subjek dianalisis berdasarkan taksonomi SOLO untuk melihat level kemampuannya. Hasil penelitian menunjukkan bahwa kemampuan subjek FD level multistructural dapat menggunakan beberapa informasi yang diberikan untuk menyelesaikan soal, namun jawaban yang diberikan kurang tepat. Upaya pemberian scaffolding untuk meningkatkan level kemampuan siswa FD dari level multistructural ke level relational terdiri dari reviewing, restructuring, dan developing contextual thinking.